Research Methodology as a Calibrator for the Validity of Scientific Research Results - Andi Agus Mandasini (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2022)
This article discusses research methodology as a calibrator (Calibration Standard) to ensure the validity of research results. Research is an activity of searching for information, data, and facts to support a perspective of truth or as a reference for the novelty of knowledge that continues to evolve with the advancement of human civilization. Therefore, a calibration standard is needed to regulate the roadmap in searching, collecting, and processing information, data, and facts into research results that can be scientifically accountable. The legitimacy of research results can only be achieved when the prerequisites of research, which include the background of the problem, formulation of the problem, research objectives and benefits, conceptual framework, and basic research theories, have been calibrated with the methodology to be used, ensuring that the results are more accurate, relevant, and can be considered valid.